A New Class of s-type X(u,v;l_p(E)) Operators - Pınar Zengin Alp; Merve İlkhan (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In thisstudy, we introduce the class of s-type X(u,v;l_p(E)) operators, L_(u,v;E). Also we show that this class is a quasi-Banach operator ideal and we study onthe properties of the classes which are produced via different types ofs-numbers.